First Thoughts. - Lewis, Helen (New Statesman, 2016)
The article discusses the ethics of working with leaked and stolen documents. The author wrote a story for Nieman Reports magazine, prompted by the Sony hack, which revealed public-interest gems like how an executive had bought pubic hair dye on Amazon. He feels whoever leaked the 2.4 terabytes of data is very brave, asserting how he or she is in the sights of every corrupt politician, state-sanctioned gangster and kleptocrat.